Pengaruh Penambahan Semen pada Tanah Lempung terhadap Parameter Konsolidasi dan Kecepatan Penurunan - Dwitya, Fara; Putra, Andius Dasa; Iswan, I (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2021)
Soil is a subgrade for basic building construction. While receiving the load, soil will settle, which take long time to complete for soft clays because of its low permeability. The problem that is caused by settlement as seen in Palembapang, Umbul Ligoh, South Lampung has low bearing capacity, this leads to cracks in the house walls, bumpy roads, and the settlement of the road constructions. One of the soil stabilization effort is addingcement as an additive material because it has very fine particles so that it can fill the soil pores and bond to the contact area between the soil grains and has a function as a strong binder. This work aimed to study the parameters of the compression index (Cc), coefficient of consolidation (Cv), consolidation settlement (Sc) and time of consolidation (t) due to soft clay mixing with cement as a soil stabilization material with percentage of 4%, 8% and 12%. Due to cement addition into soft clay, compaction with the standard proctor experienced a decrease the optimum moisture content (OMC) and an increase in the weight of maximum dry volume. In addition, in the consolidation test, the compression index (Cc) and consolidation settlement (Sc) decreased 7,95% and 5,44%, moreover the coefficient consolidation (Cv) increase 2,74% and the time of consolidation (t) were faster. The most change on consolidation parameter was recorded by the sample mixed with 12% of cement.